2021
DOI: 10.3390/cancers13153795
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Segmentation of Triple-Negative Breast Cancer (TNBC) Patient Derived Tumor Xenograft (PDX) and Sensitivity of Radiomic Pipeline to Tumor Probability Boundary

Abstract: Preclinical magnetic resonance imaging (MRI) is a critical component in a co-clinical research pipeline. Importantly, segmentation of tumors in MRI is a necessary step in tumor phenotyping and assessment of response to therapy. However, manual segmentation is time-intensive and suffers from inter- and intra- observer variability and lack of reproducibility. This study aimed to develop an automated pipeline for accurate localization and delineation of TNBC PDX tumors from preclinical T1w and T2w MR images using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…The latest report showed [ 11 ] that COAD incidence and mortality respectively rank 3 rd and 4 th in all malignant tumors, of which the incidence rose from 5 th to 3 rd in three years (2015 to 2018) according to the relevant study data, demonstrating that the incidence of COAD in China is increasing on a yearly basis. Surgical resection is still the main treatment of COAD [ 12 ], and the short-term efficacy of laparoscopic radical resection for COAD has been recognized. Clinical studies found that [ 13 , 14 ] performing laparoscopic radical resection to COAD patients who present with surgical indications can achieve the same results as an open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The latest report showed [ 11 ] that COAD incidence and mortality respectively rank 3 rd and 4 th in all malignant tumors, of which the incidence rose from 5 th to 3 rd in three years (2015 to 2018) according to the relevant study data, demonstrating that the incidence of COAD in China is increasing on a yearly basis. Surgical resection is still the main treatment of COAD [ 12 ], and the short-term efficacy of laparoscopic radical resection for COAD has been recognized. Clinical studies found that [ 13 , 14 ] performing laparoscopic radical resection to COAD patients who present with surgical indications can achieve the same results as an open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Unfreeze allows us to choose which layers of your model to train at any given time by removing them from the freeze state. This is due to the fact that the early layers of our model will already be well trained in recognizing basic lines, patterns, and gradients, whereas the later layers (which will be more specific to our aim, such as identifying parasitemia) will necessitate further training [ 36 39 ]. By fine-tuning pretrained networks, we may utilize them to recognize classes that they were not trained on in the first place.…”
Section: Process Flow and Algorithmmentioning
confidence: 99%
“…After image processing, transformation-based texture features reflect the texture and grayscale distribution within regions of interest in several locations [41]. Based on the segmented cell nucleus convex packet region, several features commonly used in these four types of texture features are extracted in this research [42][43] [44], which are: a) firstorder texture features: Variance, Kurtosis, Skewness; b) second-order texture features: GLCM [45]; c) higher-order texture features: Gray-Level Run-Length Matrix (GLRLM [46]), Gray-Level Size Zone Matrix (GLSZM [47]), Neighborhood Gray Tone Difference Matrix (NGTDM [48]); d) transform-based texture features: Median Robust Extended Local Binary Pattern (MRELBP [49]).…”
Section: ) Texture Featuresmentioning
confidence: 99%